PUBLIC SECTOR - CONCEPTUAL ELEMENTS, IMPLICATIONS IN ECONOMIC AND SOCIAL LIFE - Popa, Florina (Studies and Scientific Researches. Economics Edition, 2017)
The public economy, branch of economic science analyses the state, as economic actor; its field of research interacts with investigations of other areas of economic science (monetary, international trade, market organization etc.). The state has experienced various stages of manifestation of its role in the economy, against the changes in society, which led to either an increase in its intervention, to regulate market phenomena, the recovery of economic activity in times of crisis, or to its decline against the modernization of the economies of industrialized countries, the increase of the role of entrepreneurs, technological progress. Thus, the development of economic science, changes in economic area, the emergence of capitalism, of industrialization in the nineteenth century, especially the second half, outlined a new role towards state intervention in economic life; in the context of new economic developments of the last decades of the twentieth century, the interventionist role of the state has diminished, the state giving up certain activities, in return for initiating other actions (privatization, reducing state monopoly, deregulation).nThe paper presents conceptual elements referring to public sector, peculiarities that distinguish it from the private sector, as well as issues about the state implication in the economic life, in different periods of evolution of society.